An empirical study of China–Singapore International Land–Sea Trade Corridor: Analysis from supply and demand sides. (May 2023) - Zhu, Siying; Jia, Shuai; Sun, Qinghe; Meng, Qiang
Abstract: The China–Singapore International Land–Sea Trade Corridor (C-S-ILSTC) was officially proposed in 2018, under the government-to-government framework of the China–Singapore (Chongqing) Demonstration Initiative on Strategic Connectivity. C-S-ILSTC is expected to play an important role in the international trade and connectivity between Western China and Southeast Asia, where Chongqing serves as the logistics hub in Western China, and Singapore is a transshipment hub for Association of Southeast Asian Nations (ASEAN) region. This paper aims to analyse the newly formed intermodal freight container transport network in the context of C-S-ILSTC and China–Singapore/ASEAN region quantitatively from both supply and demand sides, and investigate C-S-ILSTC's advantages and disadvantages. For the demand side analysis, the results show that the trade volume between China and ASEAN countries is forecasted to consistently increase in recent years, and the most commonly traded cargo types between China and ASEAN have also been identified. For the supply side analysis, we examine the infrastructure and development status of the essential nodes along C-S-ILSTC. In addition, we also compare C-S-ILSTC with the conventional intermodal container transport routes connecting Western China and Southeast Asia, and discuss the development prospect of C-S-ILSTC. The results of this study could provide policy implications for the development of C-S-ILSTC and the cooperation between China and ASEAN region. Highlights: Research on the newly formed intermodal freight container transport network Quantitative analysis from both supply and demand sides Investigate the advantages and disadvantages of C-S-ILSTC Discuss the development prospect of C-S-ILSTC Provide policy implications for C-S-ILSTC development and regional cooperation